Fiscal Consolidation in Europe: Pre- and Post-Maastricht - Christophe Kamps (Kiel Institute of World Economics (IfW), 2001)
Based on a panel data model this paper investigates whether the effects of fiscal policy on national saving in Europe have changed after the Maastricht Treaty came into force. Recently Giavazzi, Jappelli and Pagano (2000) found evidence that national saving responds nonlinearly to fiscal policy when a large and persistent consolidation is undertaken. I show that their finding is not robust, one reason being that the structural budget deficit is not a time-invariant criterion for identifying episodes of large and persistent fiscal impulses. This paper proposes and analyses an alternative definition of a fiscal consolidation episode: the post-Maastricht period.
Keywords: E6; H6; H5; H3; H2; 330; Fiscal policy; national saving; budgetary consolidation; European Union; panel; Finanzpolitik; Sparen; Haushaltskonsolidierung; Wirtschaftspolitische Wirkungsanalyse; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten